Establishing the Framework to Support Bioartificial Heart Fabrication Using Fibrin‐Based Three‐Dimensional Artificial Heart Muscle. Issue 2 (20th May 2014) - Hogan, Matthew; Mohamed, Mohamed; Tao, Ze‐Wei; Gutierrez, Laura; Birla, Ravi
Abstract Only 3000 heart transplants are performed in the USA every year, leaving some 30 000–70 000 Americans without proper care. Current treatment modalities for heart failure have saved many lives yet still do not correct the underlying problems of congestive heart failure. Tissue engineering represents a potential field of study wherein a combination of cells, scaffolds, and/or bioreactors can be utilized to create constructs to mimic, replace, and/or repair defective tissue. The focus of this study was to generate a bioartificial heart (BAH) model using artificial heart muscle (AHM), composed of fibrin gel and neonatal rat cardiac myocytes, and a decellularized scaffold, formed by subjecting an adult rat heart to a series of decellularization solutions. By suturing the AHM around the outside of the decellularized heart and culturing while suspended in media, we were able to retain functional cardiac cells on the scaffold as evinced by visible contractility. Observed contractility rate was correlated with biopotential measurements to confirm essential functionality of cardiac constructs. Cross‐sections of the BAH show successful decellularization of the scaffold and contiguous cell‐rich AHM around the perimeter of the heart.